CARACTERIZAÇÃO AGRONÔMICA E ESTIMATIVA DE PARÂMETROS GENÉTICOS DE ACESSOS DE MAMONA - De Oliveira, Camila; Douradinho, Gabriel; Bortolazzo, Guilherme; Limede, Arnaldo; De Freitas, Agner; Zoz, Tiago (ANAIS DO ENIC, 2018)
-